Isu Hak Asasi Manusia dan Instrumen Perlindungan Pekerja Kapal Pesiar - Resen, Putu Titah Kawitri; Sushanti, Sukma (Prosiding Seminar Nasional Sains dan Teknologi (Senastek), 2023)
Abstract — This research aims to examine protection instruments for Indonesian cruise workers, both international and national instruments. Specifically, this research will focus on examining protection instruments for Indonesian workers who work in the cruise ship industry. This research is based on the phenomenon that almost 70 percent of workers in the cruise ship industry currently come from countries in Asia. Cruise workers from Indonesia are the second largest workforce after the Philippines. On the one hand, working on a cruise ship is still a dream for young people who are pinning their hopes on economic prosperity, but on the other hand, the global cruise industry is reported to be a tourism industry that largely ignores the human rights of its workers, especially those from developing countries. This research applies literature study and in-depth interviews with carefully selected informants to collect relevant data, which is then interpreted and analyzed based on concepts related to Tourism and Human Rights and Labor/Employment Protection. The findings of this research show that protection for cruise ship workers has been guaranteed by international and domestic instruments; however, the power of cruise ship companies in the flags of convenience system causes ship workers to remain in a condition of exploitation.   Kata Kunci — cruise industry, human rights, protection instruments, workers